INTERNALISASI NILAI-NILAI AKHLAK MELALUI PEMBELAJARAN PAI: STUDI KASUS DI SEKOLAH - Mutiah, Nur; Ramadani, Maya; Saputri, Dela Indah; Satrisno, ⁠Hengki; Irawan, Bambang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the process of internalizing moral values through Islamic Religious Education (PAI) learning at SD An-Nur, Bengkulu City. The phenomenon of moral degradation among students, such as lack of discipline, low social awareness, and inconsistency in religious behavior, indicates that value internalization has not been optimally achieved. This research uses a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The results show that the internalization of moral values occurs through three stages, namely value transformation, value transaction, and trans-internalization. However, the process has not yet reached an optimal level because there is a gap between students’ cognitive understanding and their actual behavior. Teacher strategies such as role modeling, habituation, advice, and positive reinforcement play an important role, although their effectiveness is influenced by consistency and environmental support. The study concludes that moral value internalization in PAI learning is still not fully effective and requires stronger synergy between teachers, schools, and parents.